Holocene submerged shorelines on Theologos area (Greece). - Evelpidou, N.; Pirazzoli, P.; Vassilopoulos, A.; Tomasin, A. (Zeitschrift fur Geomorphologie, 2011)
Detailed mapping of coastline around Theologos area revealed the existence of well developed permanently submerged notches 75 ± 10 cm below present mean sea level. The regional occurrence of well preserved submerged tidal notches suggests their coseismic origin. The submergence of this Holocene shoreline possibly occurred at 1894 AD. Average submergence rate of 6.08 mm/yr may be estimated by a well preserved recumbent U-shaped notch. The retreating point depth suggests that the developing period of the notch might have been of the order of as much as three thousand years. Several non in situ large rock blocks, containing marine fossils (Lithophaga, Vermetids, Serpulids) in growth position, seem to have been projected on the coast by a tsunami wave, which might have been caused by the same coseismic episode.